Itineraries for educating young people to the faith A case study at Makuyu parish - WEGOKI, Lucy (Nairobi, 2007)
This research examines the concept of de-institutionalization of institutions for persons with disabilities, highlighting some of its major causes and how organizations, NGOs governments, churches and institutes themselves are addressing the problem. The study also aims at searching the general skills and approaches of institutions where children/youth with disability are living, taken towards the concept of de-institutionalization; attitudes of the society, parents, caretakers, educators, teachers and directors towards the processand the difficulties and problems they encounter. Data collection involved participant observation in the institutions and schools, dialogue and interviews with pupils and past pupils and past pupils with disabilities, parents, educators, caretakers, teachers, institute directors; the data collection involved also reading and analyzing secondary sources. In so doing, the teacher applies the see, judge and act methodology. Among research findings is the fact that de-institutionalization process is well ebmraced by some people, pupils, institutes, parents etc. while for others it is a wrong idea. Most of the institution directors and pupils we talked to during the research would like to de-institutionalize education and care, but they are worried about the future of the process, because most of these children are not fully welcomed in mainstream schools.
Keywords: Faith education--youth